Teaching text structure in science education: What opportunities do textbooks offer? - Kooiker-den Boer, Hilde; Sanders, Ted; Evers-Vermeul, Jacqueline (Dutch Journal of Applied Linguistics, 2023)
Outcomes from a body of research on reading education stress the importance of text structure instruction and the integration of reading instruction in content learning in primary schools. We conducted an analysis of Dutch textbooks and workbooks of the seven most frequently used science teaching programs developed for grades 3-6 in order to find out to what extent these materials are appropriate for text structure instruction. The results show that the materials do offer opportunities for text structure instruction but are not suitable for a step-by-step implementation and practice of knowledge and skills related to text structure. The textbooks offer too few clear organized single-structured texts and not all text structures are sufficiently represented. Also, the  programs differ strongly in text length, text segmentation and use of introductions. Illustrations and assignments hardly connect to the text structure. We finish the paper with recommendations for educational publishers.